Analisis Pengaruh Perilaku Jasa Tenaga Penjualan terhadap Kualitas Hubungan Studi Kasus di PT Bank Cimb Niaga Tbk - , I Dewa Putu Sidan Bayupati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Purpose - The purpose of this paper is to examine salesperson service behavior to customer satisfaction and trust in order to determine a suitable framework of selling implementation to increase number of funding amount on sales division at PT Bank CIMB Niaga Tbk Design/methodology/approach â This research use qualitative methods by questionnaire, direct field inspection, interview and literature study. A questionnaire was designed match the current condition of sample (purposive sampling) and distributed to all customer of PT Bank CIMB Niaga Tbk, and follow by field inspection and interview. Extensive literature study is done to support all findings and determine the suitable framework in selling implementation. Findings - The questionnaire, inspection and literature study demonstrates several key findings: grouping factor in salesperson service behavior and the level of customer satisfaction and trust at PT Bank CIMB Niaga Tbk. Overall, the results guide to find a proper framework in the successful implementation of salesperson selling behavior within the sales division, especially in PT Bank CIMB Niaga Tbk. Research limitations - The research is subject to the normal limitations of survey research. The study is using perceptual data provided by customer of PT Bank CIMB Niaga Tbk which may not provide clear measures and the limitation number of sample. However, this can be overcome by field inspection and extensive literature study. Practical implications â This research practically useful for the Sales Manager of PT Bank CIMB Niaga Tbk in order to increase the level of training for the salesperson subordinated and salesperson service behavior can be used as reference for good sales services implementation.